Islamic Financial Literacy from a Scientific Perspective: A Bibliometric Mapping from Google Scholar (2020–2025) - M Bahril Ilmiddaviq Daviq; Hari Setiono; Nur Ainiyah (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study investigates the development and thematic evolution of Islamic Financial Literacy (IFL) research from 2020 to 2025 using bibliometric analysis. Employing tools such as Publish or Perish, VOSviewer, and Biblioshiny, data were collected from Google Scholar to identify publication trends, keyword patterns, and conceptual clusters. The findings reveal that interest in IFL research surged between 2022 and 2023, driven by growing attention to ethical finance, Shariah-compliant digital services, and supportive policies in Muslim-majority countries. However, publication output declined significantly in 2024 and 2025. Visualizations show that keywords such as syariah, literacy, and Islamic banking are central to the literature, while emerging topics such as fintech and behavioral studies are gaining relevance. The study highlights a shift from conceptual to applied research and provides evidence-based recommendations to guide future scholarly and policy efforts. Islamic financial literacy, as this study shows, is not only an economic issue but also a sociocultural and technological one that must adapt to the changing financial landscape.